2004
DOI: 10.1242/jcs.00831
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan-oligosaccharide-induced transcription of metalloproteases

Abstract: Activated dendritic epidermal Langerhans cells and metastatic tumour cells share many properties. Both cell types can invade the surrounding tissue, enter the lymphatic system and travel to regional lymph nodes. We have recently shown that fragments of the extracellular matrix component hyaluronan, which are typically produced at sites of inflammation, can activate dendritic cells. Upon activation, dendritic cells upregulate expression of matrix metalloproteases (MMPs). These observations prompted us to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
96
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 64 publications
(63 reference statements)
10
96
0
2
Order By: Relevance
“…1d demonstrates that LMW HA equally induces MIP-1␣ in TLR4 knockout and WT macrophages. Interestingly, Feiber with Termeer have also published data consistent with our findings that demonstrate that in murine embryonic fibroblasts oligosaccharide HA signals in a non-TLR4-dependent pathway (31). It is possible that different sizes of HA might signal differentially between TLR2 and TLR4.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1d demonstrates that LMW HA equally induces MIP-1␣ in TLR4 knockout and WT macrophages. Interestingly, Feiber with Termeer have also published data consistent with our findings that demonstrate that in murine embryonic fibroblasts oligosaccharide HA signals in a non-TLR4-dependent pathway (31). It is possible that different sizes of HA might signal differentially between TLR2 and TLR4.…”
Section: Discussionsupporting
confidence: 88%
“…On the basis of the ability of LMW HA to initiate inflammatory responses, we and others have hypothesized that LMW HA fragments were inducing activation via a TLR (15,(31)(32)(33). In this report, we identify TLR-2 as the HA fragment-activating receptor and demonstrate the ability of HMW HA to inhibit TLR-2 signaling.…”
mentioning
confidence: 58%
“…Although there is no consensus on the molecular mechanisms by which CD44 is linked to apoptosis (Hauptschein et al, 2005), HA fragments generated from the ECM by hyaluronidases stimulate HER2 and c-Src tyrosine kinase phosphorylation of cytoskeletal proteins, and Rho GTPase signaling, through desialylated CD44 receptor-specific networks (Ponta et al, 2003;Turley et al, 2002). As we observed in the present study, expression of CD44 itself may not change following ligand binding, depending on the cell type or basal level of CD44 expression (Ohno-Nakahara et al, 2004), but the observed increase in CD95 expression is consistent with transcription factor upregulation following HA fragment binding by desialylated CD44 (Fieber et al, 2004;Ohno et al, 2005). CD44 genes are annotated in fish, amphibian, and avian genomes, but our data establish for the first time that reptile cells also express a CD44 homolog, and further suggest that CD44-specific tyrosine kinase signaling networks are also conserved across vertebrate species.…”
Section: Discussionsupporting
confidence: 85%
“…Binding of sHA, but not lHA, to CD44 significantly increases production of the inflammatory cytokine IL-6 (23). In 3LL and embryonic fibroblasts, oHA strongly stimulates NF-B activation by an unknown HA receptor and induces expression of metalloproteases MMP-9 and MMP-13 (24).…”
mentioning
confidence: 99%